Co-occurrence of non-alcoholic steatohepatitis exacerbates psoriasis associated with decreased adiponectin expression in a murine model - Takezaki, Daiki; Morizane, Shin; Ikeda, Kenta; Iseki, Masanori; Sakamoto, Yuma; Kawakami, Yoshio; Hashiguchi, Taishi; Shirakata, Yuka; Nishina, Sohji; Mukai, Tomoyuki (Frontiers in Immunology, 2023)
Introduction. Clinical studies have suggested a bidirectional association between non-alcoholic steatohepatitis (NASH) and psoriasis, affecting each other's development and severity. Here, we explored bidirectional causal linkages between NASH and psoriasis using a murine model.NASH was induced in mice by streptozotocin injection at 2 days of age and by high-fat diet feeding (STAM™ model). Psoriasis was induced by topical application of imiquimod (IMQ) on the ear. The severities of liver damage and psoriatic skin changes were determined using histological analysis. Gene expression in the skin tissues was evaluated using quantitative PCR analysis. Serum cytokine levels were determined using enzyme-linked immunosorbent assay. To examine the innate immune responses of normal human epidermal keratinocytes (NHEKs), the cells were treated with interleukin (IL)-17A, tumor necrosis factor (TNF)-α, and AdipoRon, an adiponectin receptor agonist.Results and Discussion. There were no differences in the degree of liver tissue damage (fat deposition, inflammation, and fibrosis) between NASH mice with and those without psoriasis. Conversely, the co-occurrence of NASH significantly augmented psoriatic skin changes, represented by epidermal hyperplasia, in psoriatic mice. Pro-inflammatory cytokines were expressed in the inflamed skin of psoriatic mice, and the expression of genes, especially Il23a, Il1b, Il36g, and Mip2, was significantly upregulated by the co-occurrence of NASH. The expression of keratinocyte activation marker genes Defb4b and Krt16 was also upregulated by the co-occurrence of NASH. The serum TNF-α and IL-17 levels were increased by the co-occurrence of NASH and psoriasis. The serum adiponectin levels decreased in NASH mice compared with that in non-NASH mice. In NHEK culture, TNF-α and IL-17A synergistically upregulated CXCL1, CXCL8, and IL1B expression. The upregulated pro-inflammatory gene expression was suppressed by AdipoRon treatment, reflecting the anti-inflammatory capacity of adiponectin.The co-occurrence of NASH exacerbated psoriatic skin changes associated with increased serum inflammatory cytokine levels and decreased serum adiponectin levels. Combined with in vitro findings, increased inflammatory cytokine levels and decreased adiponectin levels likely promote innate immune responses in epidermal keratinocytes in psoriatic skin lesions. Overall, therapeutic intervention for co-occurring NASH is essential to achieve a favorable prognosis of psoriasis in clinical practice.